Seismic earth : array analysis of broadband seismograms - Levander, Alan R.; Nolet, Guust, 1945-; Wiley eBooks; American Geophysical Union (Washington, DC : American Geophysical Union, 2005)
This solid Earth book offers discussion on the current state of seismic theory with specific examples of new imaging techniques for the crust and upper and lower mantle. It also includes discussion on near future uses of, and developments in, imaging theory via proposed developments in seismic instrumentation.
Perspectives on array seismology and USArray / Alan Levander and Guust Nolet -- Case studies of seismic tomography and earthquake location in a regional context / William Menke -- Traveltimes and amplitudes of seismic waves / Guust Nolet, F.A. Dalen and Raffaella Montelli -- Seismic tomography with irregular meshes / Malcolm Sambridge and Nick Rawlinson -- Surface wave tomography applied to the north american upper mantle / Suzan van der Lee and Andrew Frederiksen -- Array analysis of two-dimensional variations in surface wave phase velocity and azimuthal anisotropy in the presence of multipathing interference / Donald W. Forsyth and Aibing Li -- Imaging three-dimensional anisotropy with broadband seismometer arrays / Karen M. Fischer [and others] -- Imaging earthquake source complexity / Satoshi Ide, Gregory C. Beroza and Jeffrey J. McGuire -- Sursurface imaging of complex structures by reflection seismic data / Biondo Biondi and Dimitri Bevc -- Imaging teleseismic P to S scattered waves using the Kirchhoff integral / Alan Levander, Fenglin Niu and William W. Symes -- Direct imaging of the coda of teleseismic P waves / Gary L. Pavlis -- Multichannel inversion of scattered teleseismic body waves / Stephane Rondenay, Michael G. Bostock and Karen M. Fischer -- Spectral-element method in seismology / Dimitri Komatitsch, Seiji Tsubio and Jeroen Tromp -- Introduction to radiative transfer of seismic waves / Ludovic Margerin.
Includes bibliographical references.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
John Wiley and Sons
Keywords: Seismograms; Seismic arrays; Seismic arrays; Seismograms; Seismometry; Earth Sciences; Electronic books